Romanticism and Impressionism. A path between Turner and Monet (Lebenswelt. Aesthetics and philosophy of experience., 2016)
The purpose of this paper is to further examine the aesthetical and theoretical relationship between the Romantic movement and French Impressionism, including its further development into pointillism and/or post-impressionism. The examination focuses on the German Romantic movement (from a theoretical viewpoint) as well as on the English Romantic movement (from a pictorial perspective: mainly, the Turner-Ruskin relationship). This hermeneutical journey takes place both through the analysis of specific works by main figures belonging to these art movements and through the examination of some of the theoretical concepts associated with their aesthetical doctrines, which have been referenced to either explicitly or implicitly.